Pengendalian Laju Korosi Baja Dalam Air Laut Dengan Menggunakan Proteksi Katodik Metoda Anoda Korban - Ayu Annisya Tri Adriana; Komalasari Komalasari; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Cathodic protection is a metal surface protection system against corrosion by direct current (DC ) from an external source to protect metal surfaces from corrosion. In this study, which the protection was employed of voltaic series sacrificial anode method, where the metal has a lower potential is used as sacrificial anodes in order to controlling carbon steel of corrosion. This research was conducted by using ASTM A36 steel in Bengkalis seawater with immersion lengths of 15, 20 and 25 days by using sacrificial anode of Al. The purpose of this research was to study the effect of cathodic protection in controlling the corrosion rate of carbon steel, determine the effectiveness of the sacrificial anode, and determine the best distance from the anode to the cathode. The design of the study was done by varying the type of anode in the form of Al , the anode to cathode distance 1 cm, 2 cm, 3 cm. Data was processed by using weight loss method with unit (mpy). The best protection occured at 15 days immersion, by using Al anode, the lowest corrosion rate is 1.448 mpy. In this study, the anode Al proved efective to protected carbon steel at a distance of 1 cm, and with an effectiveness of 69.06%.Key words: cathodic protection, corrosion rate, seawater, sacrificial anode